2009
DOI: 10.1097/olq.0b013e3181a9cc41
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of HIV Acquisition Among Men Who Have Sex With Men

Abstract: Objective To develop and validate an easy-to-use prediction model for HIV acquisition among men who have sex with men (MSM). Methods We developed prediction models using medical records data from an STD clinic (2001–2008) and validated these models using data from the control arm of Project Explore, an HIV prevention trial (1999–2003). Results Of 1903 MSM who tested for HIV more than once in the development sample, 101 acquired HIV over 6.7 years of follow-up. Annual HIV incidence was 2.57% (95% confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
169
3
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(181 citation statements)
references
References 56 publications
(61 reference statements)
4
169
3
3
Order By: Relevance
“…Studies of medication-assisted therapy to reduce methamphetamine use have, to date, mostly been negative, apart from one study of mirtazapine. 23 The proportionately greater methamphetamine use among referred participants, who were identified primarily through the STD Clinic and STD partner services, likely reflects the higher HIV/STD transmission risk among methamphetamine-using MSM 24,25 and further highlights the public health challenge of addressing methamphetamine as a barrier to HIV care and treatment and as a facilitator of HIV transmission. Many substance users did not identify their substance use as an important barrier to care.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of medication-assisted therapy to reduce methamphetamine use have, to date, mostly been negative, apart from one study of mirtazapine. 23 The proportionately greater methamphetamine use among referred participants, who were identified primarily through the STD Clinic and STD partner services, likely reflects the higher HIV/STD transmission risk among methamphetamine-using MSM 24,25 and further highlights the public health challenge of addressing methamphetamine as a barrier to HIV care and treatment and as a facilitator of HIV transmission. Many substance users did not identify their substance use as an important barrier to care.…”
Section: Discussionmentioning
confidence: 99%
“…International guidance on testing frequency from Australia (221) (234) and the USA (235) use a number of observational studies including a weighted risk assessment (236) to guide recommendations on more frequent testing in men at 'high risk' who have greater partner numbers or a history of recreational drugs use. BASHH Recommendations for Testing for Sexually Transmitted Infections in Men-who have sex-with-men 2014, derived from an expert consensus meeting in 2014 (76) suggest a much broader interpretation of MSM at 'high risk' to include any unprotected sexual contact (oral, genital or anal) with a new partner.…”
Section: Sti and Hiv Testing 231 Recall Arrangements And Frequency mentioning
confidence: 99%
“…Other tools developed for use in sexual health have achieved similar levels of performance in, for example, identifying patients at risk for chlamydia and/or gonorrhoea (AUROC curve = 0.74) 64 and identifying MSM at risk for HIV acquisition (AUROC curve = 0.67). 75 It was suggested that having children may be more likely to affect attendance among women than men and, indeed, the gender variable was excluded from the model when having children was introduced. However, univariable analysis indicated that there was a significant effect for being a mother or a father compared with having no children and this variable did not provide any additional explanatory value when incorporated into the model instead of the binary variable.…”
Section: Objective 4: Retention Risk Toolmentioning
confidence: 99%